الأردن تقييم الجاهزيّة للتجارة الإلكترونيّة - United Nations Conference on Trade; Development (United Nations, 2022)
E-commerce presents an important opportunity to address some of the major challenges faced by the Jordanian economy and to become a driver of sustainable economic growth. Jordan has experienced an economic slowdown in recent years, with GDP growth dropping from an average of 5.1% in 2000-2015 to 2.0% in 2016-2019. In addition, in 2020 the global COVID-19 pandemic had negative consequences for the Jordanian economy, albeit to a lesser degree than in neighboring economies, with GDP falling by 1.6%. The economy is gradually returning to a growth path, with an expected 1.9% increase of GDP in 2021. The Jordan eTrade Readiness Assessment aims at identifying the main barriers and opportunities for e-commerce development in the 7 eTrade for all policy areas by providing a detailed diagnostic of the digital ecosystem and identifying key policy actions for which support can be mobilized. The information provided in this report is based on qualitative and quantitative data collected from: i) desk research, ii) responses from the 3 online surveys (public, private, and consumer), iii) the results of the national multi-stakeholder and bilateral consultations, and iv) specific contributions made by eT4a and development partners.